Myiasis in A Chronic Untreated External Ear Lesion: A Case Report - Semme, Muhammad Yatsrib; Abidin, Mohammad Reza Zainal (Universitas Negeri Gorontalo, 2025)
Myiasis is a prevalent parasitic infection which predominantly observed in rural regions among humans. In the practice of otolaryngology, this medical condition has the potential to impact the auditory organs, nasal passages, paranasal sinuses, nasopharynx, oral cavity, and the integumentary system of the craniofacial region. We reported a case in a 77-year-old woman who came to the emergency department due to chronic ear pain followed by the emergence of maggots. The chronic wound in the ear is the culprit in this condition. Dipterous larvae undergo their life cycle within the body of vertebrates which are attracted to open wounds. The primary objective in the treatment of myiasis is the eradication of maggots. In this case, we present successful treatment of aural myiasis following the complete removal of the maggot and treating the underlying condition. This case taught the lesson that myiasis could affect the human auditory system, especially in chronic untreated ear lesions with poor sanitation. Removing the larva and treating the underlying disease is the key treatment.Keywords: Earache, myiasis, larva